Correlation between TSH, Prolactin, LH, FSH, Estrogen, and Progesterone in Women with Infertility - Khambalkar, Shobha D.; Jadhav, Krishna Nitin (International Journal of Integrated Health Sciences, 2025)
Background: Hormonal imbalances play a pivotal role in female infertility, affecting various endocrine pathways that warrant comprehensive evaluation.Objective: To analyze correlations between thyroid-stimulating hormone (TSH), prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), estrogen, and progesterone in women with infertility.Methods: This retrospective observational study was conducted at the Department of Obstetrics and Gynecology of Prakash institute of Medical Sciences, India, between January 2024 and December 2024. Medical records of 140 women (90 with primary infertility and 50 with secondary infertility) aged 19–45 years were analyzed over a one-year period. Hormonal profiles including TSH, prolactin, LH, FSH, estrogen, and progesterone were analyzed. Statistical analyses were performed using the SPSS 23.0 software and  a p-value of less than 0.05 was considered statistically significant.Results: Women with primary infertility were younger and had a shorter duration since marriage compared to those with secondary infertility (p<0.001). Irregular menstrual cycles were significantly more common in primary infertility cases (p=0.002). Thyroid dysfunction was seen in 25% of cases, with hypothyroidism as the most common thyroid function abnormality (14.9%). A strong positive correlation was found between TSH and prolactin levels (r=0.821, p<0.05), whereas a significant negative correlation was present between TSH and LH (r=-0.73, p<0.05) and FSH (r=-0.41, p<0.05). Correlations between TSH and estrogen or progesterone was not found to be statistically significant (P>0.05).Conclusion: TSH levels significantly correlate with prolactin, LH, and FSH levels in women with infertility. These findings underscore the importance of comprehensive endocrine evaluation of women with infertility to optimize diagnosis and management strategies.